2022
DOI: 10.1186/s12887-022-03218-0
|View full text |Cite
|
Sign up to set email alerts
|

Protocol and programme factors associated with referral and loss to follow-up from newborn hearing screening: a systematic review

Abstract: Background An effective newborn hearing screening programme has low referral rate and low loss to follow-up (LTFU) rate after referral from initial screening. This systematic review identified studies evaluating the effect of protocol and programme factors on these two outcomes, including the screening method used and the infant group. Methods Five databases were searched (latest: April 2021). Included studies reported original data from newborn he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…LTFU was the main problem throughout the two years of screening. LTFU is not only a serious problem in low-income countries and middle-income countries but was also found in NHS programmes in high-income countries [ 33 , 34 , 35 ]. In our study, LTFU was highest in the MG maternity hospital where the most infants were born and the workload per screener was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…LTFU was the main problem throughout the two years of screening. LTFU is not only a serious problem in low-income countries and middle-income countries but was also found in NHS programmes in high-income countries [ 33 , 34 , 35 ]. In our study, LTFU was highest in the MG maternity hospital where the most infants were born and the workload per screener was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Four scenarios are proposed to explain low diagnostic testing completion rates, the first three of which have previously been well-explored in the literature: (1) states may have insufficient diagnostic capacity (e.g., lack of screening equipment or pediatric audiologists, as highlighted in Shulman et al 2010), (2) states may have high diagnostic capacity that remains under-utilized due to lack of provider knowledge (under-emphasis of positive screen actionability) or family socioeconomic barriers (Shulman et al 2010; Cree et al 2022), (3) states may have otherwise adequate diagnostic capacity but are overwhelmed by a high volume of false-positive screens due to poor screening specificity (Clemens & Davis 2001; Mackey et al 2022), or (4) diagnostic testing completion rates may be higher than documented due to underreporting of completed diagnostic test results to state EHDI programs (Shulman et al 2010 acknowledges information gaps and found hearing results missing in records). The authors intend to explore these potential contributors to low diagnostic testing rates further in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, two methods are internationally recommended as screening technologies: detection of transient evoked otoacoustic emissions (TEOAE) which record the response of the cochlear outer hair cells to a click or tone-burst stimulus, and automatic auditory brainstem response (AABR) detection which records neurophysiological responses from the brainstem to acoustic stimuli and, therefore, reflects the function of the cochlea, auditory nerve and brainstem. Both methods have high sensitivity and specificity, provided that ideal conditions for measurement such as experienced screening staff and a quiet setting are available [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although AABR screening is associated with a lower referral rate than TEOAE screening [ 2 , 3 ], neonates without an increased risk of hearing loss are often initially screened with TEOAE owing to the simplicity and rapidness of measurement compared to AABR. AABR screening is recommended for newborns with an increased risk of hearing impairment, [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%